Static Verification for Code Contracts - Fahndrich, Manuel (SAS'10 Proceedings of the 17th international conference on Static analysis, 2010)
The Code Contracts project at Microsoft Research enables programmers on the .NET platform to author specifications in existing languages such as C# and VisualBasic. To take advantage of these specifications, we provide tools for documentation generation, runtime contract checking, and static contract verification. This talk details the overall approach of the static contract checker and examines where and how we trade-off soundness in order to obtain a practical tool that works on a full-edged object-oriented intermediate language such as the .NET Common Intermediate Language.